2015
DOI: 10.5539/ijbm.v10n6p90
|View full text |Cite
|
Sign up to set email alerts
|

International Hotel Strategy and Institutional Distance: A Conceptual Framework

Abstract: In recent international hotel strategy literature, institutional differences between home and host country have been mostly neglected. Although concepts such as institutional distance have become more prevalent as analytical tools in the mainstream international business literature, not much of it has so far been adopted in the wider field of international hospitality management. The objective of this article is to propose a conceptual framework that is based on insights from new institutional economics in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Age is an important ingredient as it provides firms with the necessary experience to recognize and integrate external opportunities (Amankwah-Amoah et al, 2019; Siggelkow & Levinthal, 2003). Furthermore, we included competencies of the subsidiary and relative size (Birkinshaw, Hood, & Jonsson, 1998), home region and industry (Dahms, 2015(Dahms, , 2017Dahms, Kingkaew, & Ng, 2021), and entry mode (Hennart, 2009). The full model is illustrated in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is an important ingredient as it provides firms with the necessary experience to recognize and integrate external opportunities (Amankwah-Amoah et al, 2019; Siggelkow & Levinthal, 2003). Furthermore, we included competencies of the subsidiary and relative size (Birkinshaw, Hood, & Jonsson, 1998), home region and industry (Dahms, 2015(Dahms, , 2017Dahms, Kingkaew, & Ng, 2021), and entry mode (Hennart, 2009). The full model is illustrated in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…This is due in large measure because the efficiency of assets, especially those transferred from the home country of the MNE, often varies with the institutional context in which they developmentally originated. Several assets are highly context dependent, for instance, studies have indicated that subsidiaries develop different density of interorganizational and intraorganizational network relationships depending on the economic and institutional development level of the host country (e.g., Cheng & Huang, 2020;Dahms, 2015;Drori & Honig, 2013;Úbeda-García et al, 2020). This will likely impact the way in which ambidextrous network management is configured for higher performance outcomes.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Service sector subsidiaries are challenged in different ways compared to their manufacturing peers (Iwanicz-Drozdowska and Witkowski, 2021; Kundu and Lahiri, 2015; Rugman and Verbeke, 2008). For instance, their output is far more often subject to local demand adaptation as compared to relatively homogenous manufacturing goods (Yamin, 1999; Dahms, 2015). This impacts how useful home country grown firm-specific advantages in the form of competencies are for the subsidiary (Philippe and Léo, 2011; Rugman and Verbeke, 2008).…”
Section: Introductionmentioning
confidence: 99%